Oikeusvaltioperiaate ja riippumattomat tuomioistuimet - Heikkilä, Satu (Lakimies, 2024)
The rule of law and independent courts and tribunals The Venice Commission’s Rule of Law Checklist is an excellent tool for structuring the concept of the rule of law. In addition, the various elements of the principle have been largely concretised in the case-law of the European Court of Human Rights, which has established more detailed practices. Although the latest reports indicate that judicial independence is satisfactory in most Council of Europe Member States and that the depoliticisation of the processes of appointing supreme court judges has developed positively over the last two years, there is still a need to protect the appointment, promotion, evaluation and disciplinary measures concerning judges against possible undesirable influence. In Finland, the appointment procedure for permanent judges is in line with the recommendations of the Venice Commission and does not appear to be based on political or personal considerations at any structural level. On the other hand, the situation in Finland is more problematic for fixed-term judges. The situation in Finland appears to be positive with regard to the right of judges to remain in office and their dismissal, and there does not appear to be any signs of external pressure in Finland either. As far as Finland is concerned, there does not appear to be any question of widespread distrust of the judiciary.